PERBEDAAN RESILIENSI MAHASISWA DI TINJAU BERDASARKAN ETNIS - Satrianti, Rara; Sujadi, Eko; Ahmad, Bukhari (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
Resilience is the ability to overcome and adapt to difficult events or major problems that occur in life. The aim of this research is to examine differences in student resilience based on ethnicity. This research design used a descriptive and comparative survey, involving 176 students from universities in Kerinci, Java, Melayu Jambi, Batak, Minang Kabau. The research adapts differences in student resilience based on ethnicity for data collection. Data analysis using the results of the Kruskall-Wallis technique. The results show that student resilience is in the high category. This study shows that resilience has a big influence on students. This research has important implications regarding student resilience to reduce student resilience.